Where and how does fundamental care fit within seminal nursing theories: A narrative review and synthesis of key nursing concepts. Issue 19 (7th August 2020) - Mudd, Alexandra; Feo, Rebecca; Conroy, Tiffany; Kitson, Alison
Abstract: Aims and objectives: To elucidate the synergies between fundamental care and seminal nursing theories. Background: Nursing theories are often criticised for their limited clinical relevance, with the existence of a theory‐to‐practice gap widely acknowledged. Pervasive examples of poor‐quality care, particularly for people's most fundamental needs, raise questions as to whether nursing theories sufficiently prioritise fundamental care. The Fundamentals of Care Framework (hereinafter "the Framework") represents a valid, comprehensive and evidence‐based description of fundamental care. The Framework captures the complexity and multidimensionality of fundamental care delivery, predicated on the nurse–patient relationship; integration of physical, psychosocial and relational needs; and a supportive context. Despite strong face validity, the Framework's alignment with seminal nursing theories remains unexplored. Design: Narrative review. Method: Twenty‐nine seminal nursing theories were included. Categories for analysis were developed inductively and deductively, focusing on the themes of relationship, integration of care, context and the theories' ease of use. Results are reported in accordance with PRISMA‐ScR guidelines. Results: Though relationship, integration of care and context and were features shared across a number of nursing theories, no single theory depicts these collectively to the same extent as the Framework. In particular, integration of physical, psychosocial and relational aspects of care was found to be poorly described in the theories. Conclusion: Failure to account for integration of care means that nursing theories continue to conceptualise fundamental care as a series of discrete tasks. To ensure relevance at the point of care, future nursing theories must accurately reflect the complexities of fundamental care delivery, specifically the need to integrate multiple care needs simultaneously, alongside being straightforward to apply in practice. Relevance to clinical practice: Bridging the theory‐to‐practice gap requires a nursing discourse that is relevant at the point of care. We provide suggestions for how future nursing theories can bridge this gap.